New Trends of Indonesia’s Foreign Policy Under President Joko Widodo in The First Period - Setiawati, Siti Mutiah; Roziqin, Ali (Technium Social Sciences Journal, 2024)
President Joko Widodo inherited many domestic and foreign political problems and opportunities inherited from the previous President. This article aims to analyze Indonesia’s foreign policy during the first term of President Joko Widodo. This research is qualitative research that utilizes data to find solutions to problems based on existing social realities using scientific methods. The findings are that the Indonesian government under President Joko Widodo has carried out foreign cooperation, especially focusing on the pillars of security and peace, economic and maritime diplomacy, protection of Indonesian citizens and legal entities abroad as well as ASEAN cooperation to strengthen Indonesia as the world’s maritime axis. Apart from that, cooperation with various countries in East Asia focuses on economic opportunities and infrastructure development, especially from China and South Korea. This tendency will give rise to rivalry in the East Asia region, making it difficult to build a strong regional organization that is needed for harmonious ASEAN-East Asia cooperation because these two regions are close together.